2016
DOI: 10.18632/oncotarget.7954
|View full text |Cite
|
Sign up to set email alerts
|

CWP232228 targets liver cancer stem cells through Wnt/β-catenin signaling: a novel therapeutic approach for liver cancer treatment

Abstract: Liver cancer stem cells (CSCs) are resistant to conventional chemotherapy and radiation, which may destroy tumor masses, but not all liver CSCs contribute to tumor initiation, metastasis, and relapse. In the present study, we showed that liver CSCs with elevated Wnt/β-catenin signaling possess much greater self-renewal and clonogenic potential. We further documented that the increased clonogenic potential of liver CSCs is highly associated with changes in Wnt/β-catenin signaling and that Wnt/β-catenin signalin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 58 publications
2
48
1
Order By: Relevance
“…CWP232228, PRI-724, and ipafricept are reported to decrease CSC marker expression, inhibit tumor spheroid formation, and decrease tumor metastasis. [45][46][47] b-Catenin-TCF4 complex formation is the ultimate and functional step in activating the canonical Wnt signaling to b-catenin pathway, and this interaction is considered an attractive target for cancer therapy. 48 In this study, we found that TRIB3 increases the association between b-catenin and TCF4 by tethering these proteins together.…”
Section: Discussionmentioning
confidence: 99%
“…CWP232228, PRI-724, and ipafricept are reported to decrease CSC marker expression, inhibit tumor spheroid formation, and decrease tumor metastasis. [45][46][47] b-Catenin-TCF4 complex formation is the ultimate and functional step in activating the canonical Wnt signaling to b-catenin pathway, and this interaction is considered an attractive target for cancer therapy. 48 In this study, we found that TRIB3 increases the association between b-catenin and TCF4 by tethering these proteins together.…”
Section: Discussionmentioning
confidence: 99%
“…We used this concentration in functional and molecular analyses to minimize the effect on cellular proliferation. Previously, we have discovered that Wnt/b-catenin signaling is activated to a greater extent in tumor cells than in normal cells and that it is further enhanced in CSC populations for regulating self-renewal activity and chemoresistance (29,33,34). Therefore, we hypothesized that niclosamide might target CSCs by inhibiting Wnt/b-catenin signaling.…”
Section: Niclosamide Inhibits Cancer Stemness and Therapy Resistance mentioning
confidence: 99%
“…166 The small-molecule inhibitor CWP232228 antagonizes the binding of β-catenin to TCF in the nucleus to induce apoptosis in liver CSCs. 167 In addition, temozolomide combined with miR-125b significantly induces apoptosis by targeting the Wnt/β-catenin signaling pathway in glioma stem cells. 168 Wnt/β-catenin signaling has been implicated in CSC-mediated metastasis.…”
Section: Major Signaling Pathways In Cscsmentioning
confidence: 99%